Par-dessus l’épaule du maître. Approche matérielle de l’adaptabilité artisanale médiévale : l’exemple des « brocarts appliqués » savoyards - Ariane Pinto (Bulletin du Centre d’Études Médiévales d’Auxerre)
Materials are a major part of art works evocative power. Physico-chemical analyses allows one to delve into the object in order to collect crucial information on the raw materials used and various steps of the manufacturing process. As ancient written sources can be sparse, a material approach can provide crucial data regarding artists and craftsmen’s technical processes and choices. In this article, we studied thirteen sculptures from the ancient Savoy Duchy. Dated from the end of the 15th and the beginning of the 16th century, they display « tin-relief applied brocades » attempting to mimic precious silk fabrics enhanced with gold or silver threads and highly pursued by medieval elites. By comparing written sources and results from physico-chemical analyses for each step of the « chaîne opératoire », we highlighted the variability of practices and the adaptability of craftsmen. We also offered a conclusive identification of the type of craftsmen responsible for this decoration.